Why Blended Learning Format? - Караєва, Тетяна В'ячеславівна; Караева, Татьяна Вячеславовна; Karaieva, Tetiana (My University, 2020)
The purpose of the article is to make learners interact with online content by means of introducing the blended learning format at the expense of providing their learning autonomy as well as the share of personal responsibility for the results of language learning acquisition in the course of developing learners autonomy.
Keywords: teaching foreign languages; students; learning process